Improving theatre turnaround time. Issue 1 (10th February 2017) - Fletcher, Daniel; Edwards, David; Tolchard, Stephen; Baker, Richard; Berstock, James
Abstract : The NHS Institute for Innovation and Improvement has determined that a £7 million saving can be achieved per trust by improving theatre efficiency. The aim of this quality improvement project was to improve orthopaedic theatre turnaround without compromising the patient safety. We process mapped all the stages from application of dressing to knife to skin on the next patient in order to identify potential areas for improvement. Several suggestions arose which were tested in multiple PDSA cycles in a single theatre. These changes were either adopted, adapted or rejected on the basis of run chart data and theatre team feedback. Successful ideas which were adopted included, the operating department practitioner (ODP) seeing and completing check-in paperwork during the previous case rather than during turnaround, a 15 minute telephone warning to ensure the next patient was fully ready, a dedicated cleaning team mobilised during wound closure, sending for the next patient as theatre cleaning begins. Run charts demonstrate that as a result of these interventions the mean turnaround time almost halved from 66.5 minutes in July to 36.8 minutes over all PDSA cycles. This improvement has been sustained and rolled out into another theatre. As these improvements become more established we hope that additional cases will be booked, improving theatre output. The PDSA cycle continues as we believe that further gains may yet be made, and our improvements may be rolled out across other surgical specialities.